The Characterizations and Studies of Chemical Bath Deposited Ni3Pb2S2 Thin Films for Solar Cell - Ho, Soon Min (INTI International University, 2019)
Currently, thin films have high potential for use in optoelectronic and solar cell applications due to appropriate band gap value. There are many deposition techniques have been used to prepare thin films including physical and chemical method. Chemical bath deposition technique was used to produce thin films. This technique has many advantages such as can control film thickness, quality of sample, and deposition rate. In this work, Ni3Pb2S2 films were deposited onto glass slide from aqueous solutions. Characterization of obtained films were investigated by using various tools. X-ray diffraction, atomic force microscopy and UV-visible spectrophotometer were employed to investigate the structure, topography and optical properties of films. Photovoltaic parameters were studied using a simulated AM1.5 Global spectrums. The obtained nanostructured thin films indicated band gap of 1.4 eV. Optical properties exhibited higher absorption in ultraviolet region, while lower absorption could be observed in infrared region. These ternary compounds indicated efficiency of 2.7 % based on power conversion efficiency testing.